Battery Powered Mini-Excavator. (26th November 2018) - Prochazka, Petr; Pazdera, Ivo; Cipin, Radoslav; Vorel, Pavel; Knobloch, Jan
Abstract : The paper deals with design of electric drive for two-tons mini-excavator powered from Lithium battery. Utilization of battery powered excavator has significant benefit in closed areas where the excavators with combustion engine are uncomfortable for working staff. The paper describes the other operational advantages of electric drive in comparison with combustion engine and defines the requirements on battery pack.